ANTIOXIDANT ACTIVITY O}- VARIOUS SHELLS EXTRACTS FROM FOUR SPECIES OF FABACEAE WITH DPPH AND FRAP ASSAYS - Puspitasari, Nuraini
Background and obiectives: tr4a y things may halm health condition, such as lree radicals. lultheflrore antioxidants are needcd 1() neutralize liee rcdicals aclions. Many plants has anlioxidant aclivity including several nut and bean. Fabaceae family contained phenolic and flavonoid compounds. The aim olthis research were to study a tioxidant activitv of various shells extracts frorn lour species of Fabaccac using lwo methods ol a tioxidant resliig DPPH (2-2-diphenyl-1 picryihydrazyl), FRAP (Ferric Reduclng Antioridant Power) and its corelation with total phenolic, llavonoid and carotenoid cortent Nlethod: Extraction was perlonDcd by reflux using gradient polarity sohelrt. Lach extract were obsened by thin layer chromatography (TLC), andoxidant aclivity by DPPH,II{{P assays, lcjo of DPPH scalenging activity, ECt0 of I'RAP capacity. detelminalion of rotal phcnolic. IlavoDoid and carolenoid content rrere perlomcd by spectrophotometry UV-Vis aftl its conclation with DPPII and FRAP capacities by Pearson meilod. Result: The highest DPFH scaverging aclivily (75.97 %) was givcn by ethancl sliells extmct ol peairut and the highesr FRAP capaciry (16-:15 %) 1l,as given by heranc shells extmct of kidney beao. Ethanolic shclls extract ol peanut had lhc highest phenolic oontcnt (6.91 g GAE/100 g) and ethyl acetalc shells extmct of peanut had the highest total flavonoid (13.37 g QE/100 g). ethyl acetate shells exlract oi soybean had the highest carotenoid 0.33 g BIjT,/100 g. Total phenolic of aIl ofshelis exl.acts Lom tbur species ollabaceac (solbean. red kidney bean, bogor peanut and peanut) had highly positive colrelation with DPPH scavenging activity (r = 0.732, p<0.05. r = 0.985, p< 0.01. r:0.E4,+- p.:O.{li, r = 0.984, p<0.01) Conclusion: All of extracts sample (except n hcxanc shelis exiract ol so_vbean) could be olassilied as vcry slrong anlioxidant. Phenolic compoulrds were thc major contributor in extracl offour species ofFabaceae in DPPII scarcnging activities.